Elements of the heterocyst‐specific transcriptome unravelled by co‐expression analysis in Nostoc sp. PCC 7120. (20th May 2019) - Brenes‐Álvarez, Manuel; Mitschke, Jan; Olmedo‐Verd, Elvira; Georg, Jens; Hess, Wolfgang R.; Vioque, Agustín; Muro‐Pastor, Alicia M.
Summary: Nitrogen is frequently limiting microbial growth in the environment. As a response, many filamentous cyanobacteria differentiate heterocysts, cells devoted to N2 fixation. Heterocyst differentiation is under the control of the master regulator HetR. Through the characterization of the HetR‐dependent transcriptome in Nostoc sp. PCC 7120, we identified the new candidate genes likely involved in heterocyst differentiation. According to their maximum induction, we defined E‐DIF (early in differentiation) and L‐DIF (late in differentiation) genes. Most of the genes known to be involved in the critical aspects of heterocyst differentiation or function were also classified into these groups, showing the validity of the approach. Using fusions to gfp, we verified the heterocyst‐specific transcription of several of the found genes, antisense transcripts and potentially trans‐acting sRNAs. Through comparative sequence analysis of promoter regions, we noticed the prevalence of the previously described DIF1 motif and identified a second motif, called DIF2, in other promoters of the E‐DIF cluster. Both motifs are widely conserved in heterocystous cyanobacteria. We assigned alr2522 as a third member, besides nifB and nifP, to the CnfR regulon. The elements identified here are of interest for understanding cell differentiation, engineering of biological nitrogen fixation or production of O2 ‐sensitive molecules in cyanobacteria.